Severe acute respiratory syndrome coronavirus 2 in pregnant women: an observational study - Joshi D., Suyajna; G., Vijayalakshmi; N., Kavya; Rajeswari, Rai; Banu, Ruksar; ., Jayasakthi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an emergency health delinquent, with increase in cases worldwide. Pregnant women with COVID-19 positive status are also on rise and reported complications that occur to them during pregnancy, delivery and puerperium accentuates the need for superior care. Methods: This is a prospective cross sectional observational study of 133 pregnant COVID-19 positive patients delivered at District Hospital, Bellary, Karnataka during the period June 2020 to September 2020. Results: In the present study 87.9% were in age 20 to 30 years. 96.3% patients belong to lower socio-economic status. 4.5% patients had mild anaemia, 11.2% had moderate anaemia and 4.5% had severe anaemia. Non-severe pre-eclampsia was present in 11.2% of the patients, severe pre-eclampsia in 12% and 0.7% had gestational hypertension. Mode of delivery was 17.4% Full term normal delivery (FTND), 9% Full term vaginal delivery (FTVD), emergency Lower segment caesarean section (LSCS) in 67.7% cases and preterm delivery was seen in 4.5% of the cases. Elevated levels of D-dimer were found in 9.7% of the cases. One maternal death was reported in the study due to COVID-19 pneumonia. Conclusions: This study evaluates the obstetric and clinical outcome in COVID-19 positive patients who are in labor. Although our conclusions are limited, the findings obtained are important for understanding the clinical parameters, obstetric parameters and perinatal outcome.